2014
DOI: 10.1534/g3.114.014159
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Mediates Efficient Conditional Mutagenesis inDrosophila

Abstract: Existing transgenic RNA interference (RNAi) methods greatly facilitate functional genome studies via controlled silencing of targeted mRNA in Drosophila. Although the RNAi approach is extremely powerful, concerns still linger about its low efficiency. Here, we developed a CRISPR/Cas9-mediated conditional mutagenesis system by combining tissue-specific expression of Cas9 driven by the Gal4/upstream activating site system with various ubiquitously expressed guide RNA transgenes to effectively inactivate gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 32 publications
0
83
0
Order By: Relevance
“…Although CRISPR mutagenesis using stable transgenic lines expressing both cas9 and sgRNA have been used for generating both germline and somatic mutations in nonvertebrate models such as Caenorhabditis elegans and Drosophila melanogaster (Port et al 2014;Shen et al 2014;Xue et al 2014), it has not been reported in vertebrates until our manuscript was being revised (Ablain et al 2015). A Cas9 knock-in mouse line has been used to achieve tissue-specific mutagenesis (Platt et al 2014;Swiech et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although CRISPR mutagenesis using stable transgenic lines expressing both cas9 and sgRNA have been used for generating both germline and somatic mutations in nonvertebrate models such as Caenorhabditis elegans and Drosophila melanogaster (Port et al 2014;Shen et al 2014;Xue et al 2014), it has not been reported in vertebrates until our manuscript was being revised (Ablain et al 2015). A Cas9 knock-in mouse line has been used to achieve tissue-specific mutagenesis (Platt et al 2014;Swiech et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It can easily be adapted for use in species other than the zebrafish by modifying the codon-optimized Cas9 and U6 promoter sequences. Note that systems for tissue-specific gene inactivation have also been developed in fly and worm (Shen et al, 2014; Xue et al, 2014). We have also added a second U6:gRNA cassette in the vector backbone to allow for multiplexing.…”
Section: Discussionmentioning
confidence: 99%
“…By using different patterns of Gal4 expression, tissue-or stage-specific gene editing can be realized. These strategies have proved feasible in B. mori and Drosophila [84][85][86].…”
Section: Challengesmentioning
confidence: 99%